Letter from Joseph Scheerer & Co., December 1, 1885 - Joseph Scheerer & Co.::::::author::: (1885)
Office of Joseph Scheerer & Co., 1630 to 1634 Market Street. Branch, 22 Montgomery Street. San Francisco, Dec 1 1885 A. Walker Esq Dear Sir Mr Scheerer has been expecting to go down to San Luis, and this is why we have neglected Ah Luis' bill. Please send us the bill and we will give the matter our immediate attention. Respectfully, Jos. Scheerer & Co